2018
DOI: 10.1111/jopr.12731
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sintering Time on the Marginal Fit of Zirconia Copings

Abstract: Different sintering times did not alter the marginal fit of the zirconia copings. The mean values of the marginal gap were within the clinically acceptable level for all three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
(91 reference statements)
1
20
0
Order By: Relevance
“…In this study, both the particle size and content of PEG affected the porosity, as well as the pore distribution of the scaffolds, resulting in PTSDP scaffold groups characterized by variable compressive strength (CS), which range from 0.20 ± 0.03 to 1.57 ± 0.27 MPa for samples manufactured using PEGPs as shown in Figure 2D . The reduction in CS associated with increasing porosity has been observed in other ceramics ( Xu et al, 2015 ; Khaledi et al, 2018 , 2019 ). Overall, the CS appears to decrease as the amount of PEG increases regardless of the PEGP size.…”
Section: Resultssupporting
confidence: 58%
“…In this study, both the particle size and content of PEG affected the porosity, as well as the pore distribution of the scaffolds, resulting in PTSDP scaffold groups characterized by variable compressive strength (CS), which range from 0.20 ± 0.03 to 1.57 ± 0.27 MPa for samples manufactured using PEGPs as shown in Figure 2D . The reduction in CS associated with increasing porosity has been observed in other ceramics ( Xu et al, 2015 ; Khaledi et al, 2018 , 2019 ). Overall, the CS appears to decrease as the amount of PEG increases regardless of the PEGP size.…”
Section: Resultssupporting
confidence: 58%
“…A clinically acceptable marginal gap for dental prostheses has been debated in the literature (Christensen, 1966;Fransson, Oilo, & Gjeitanger, 1985;McLean & Fraunhofer, 1971;Nawafleh, Mack, Evans, Mackay, & Hatamleh, 2013 et al, 2019). A study (Ahmed et al, 2019) found a significant interaction between crown thickness, finish line width and sintering protocol on the marginal fit of zirconia crown; meanwhile, another study (Khaledi et al, 2019) did not find a significant difference among three different sintering times on the adaptation of zirconia copings.…”
Section: Discussionmentioning
confidence: 96%
“…None of the studies evaluated the effect of aging on the marginal and internal adaptation of zirconia restoration. Few studies have attempted to evaluate the effects of sintering parameters on the mechanical properties of zirconia or to compare conventional sintering techniques (Almazdi, Khajah, Monaco Jr., & Kim, 2012;Ersoy, Aydo gdu, De girmenci, Çökük, & Sevimay, 2015;Kim, Ahn, Kim, Kim, & Kim, 2013;Marinis et al, 2013;Sulaiman et al, 2015) and only two have investigated the effects of using different sintering protocols on marginal fitting (Ahmed et al, 2019;Khaledi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Khaledi et al evaluated the effect of 3 sintering times using a single 1530°C sintering temperature and found no significant influence of sintering times on the marginal fit of zirconia 3Y‐TZP copings. The results of this study, however, showed that FS resulted in greater marginal gaps than standard sintering protocol.…”
Section: Discussionmentioning
confidence: 99%
“…A few in vitro studies have recently shown that a combination of high sintering temperatures with short sintering times increased the flexural strength of zirconia and enhanced its optical properties . Additionally, a recent in vitro study showed that altering the sintering times does not affect the marginal fit of zirconia copings …”
mentioning
confidence: 99%